Light-induced psbA translation in plants is triggered by photosystem II damage via an assembly-linked autoregulatory circuit - Chotewutmontri, Prakitchai; Barkan, Alice (Proceedings of the National Academy of Sciences - PNAS, 2020)
The D1 reaction center protein of photosystem II (PSII) is subject to light-induced damage. Degradation of damaged D1 and its replacement by nascent D1 are at the heart of a PSII repair cycle, without which photosynthesis is inhibited. In mature plant chloroplasts, light stimulates the recruitment of ribosomes specifically to psbA mRNA to provide nascent D1 for PSII repair and also triggers a global increase in translation elongation rate. The light-induced signals that initiate these responses are unclear. We present action spectrum and genetic data indicating that the light-induced recruitment of ribosomes to psbA mRNA is triggered by D1 photo-damage, whereas the global stimulation of translation elongation is triggered by photosynthetic electron transport. Furthermore, mutants lacking HCF136, which mediates an early step in D1 assembly, exhibit constitutively high psbA ribosome occupancy in the dark and differ in this way from mutants lacking PSII for other reasons. These results, together with the recent elucidation of a thylakoid membrane complex that functions in PSII assembly, PSII repair, and psbA translation, suggest an autoregulatory mechanism in which the light-induced degradation of D1 relieves repressive interactions between D1 and translational activators in the complex. We suggest that the presence of D1 in this complex coordinates D1 synthesis with the need for nascent D1 during both PSII biogenesis and PSII repair in plant chloroplasts.